High level of serovar copenhageni detection in dog sera from Patrocínio, MG, Brazil (Bioscience Journal, 2020)
This study aimed to evaluate the occurrence of canine leptospirosis and the possible risk factors associated with the disease in the municipality of Patrocínio, MG, Brazil. A cross-sectional observational study was carried out from July through August 2017.  The municipality was divided into four regions (north, south, east and west) and a predefined number of neighborhoods (25) were randomly sampled in each region. Samples of blood serum were collected from 241 domiciled male and female dogs of different breeds and ages. To investigate the risk factors for canine leptospirosis, the owners of the animals were asked to fill out an epidemiological questionnaire. The following factors were evaluated: breed, sex, age, presence of rodents, type of diet, access to the street, vaccination, presence of flooded areas, and educational level of the owners. Blood serum samples were evaluated by the Microscopic Agglutination Test (MAT), using a collection of 24 live antigens. Of the 241 dogs evaluated, 32 (13.2%) were reactive. The most frequent serovars were: Copenhageni (37.5%) and Canicola (21.8%), followed by Icterohaemorrhagiae and Grippotyphosa (12.5%), Pomona, Tarassovi and Butembo (9.3%) and Hardjo (6.2%). The presence of canine leptospirosis was associated with purebred dogs (OR=0.3059 [95% CI: 0.1430 – 0.6547]) and vaccination (OR=2.581 [95% CI: 1.198 – 5.563]). It was concluded that some dogs in the municipality of Patrocínio, MG have anti-Leptospira spp. antibodies and that the serovars most frequently identified were Copenhageni (37.5%) and Canicola (21.8%). Pure breeds and vaccination were factors associated with the prevalence of infection.